SERANGAN KUMBANG AMBROSIA PADA KAYU SUNGKAI (PERONEMA CANESCENS) - Paimin Sukartana (Jurnal Penelitian Hasil Hutan, 1990)
Susceptibility of sungkai wood (Peronema canescens) to ambrosia  beetle infestations   was studied. Fresh cut sungkai poles, measuring about 20 cm in diameter and 75 cm in length, were selected  for the test. Six pole  treatments were chosen each of which was represented by five replications. The  test poles  were kept under shade near felling site.   Observations were respectively made for the  number  of  ambrosia  beetle tunnels  occuring  on  the pole  surface  after  3, 6, 9, 15, and 40 days. The  development pattern of the beetle  gallery system, based on  number  of  tunnel  showed  up  on some  peeling  off areas of some  consecutive  depth  of  the heaviest  infested  test pole,  was also observed.The  result shows that unbarked (with and without  flint kote) poles are practically   unattack by the borer. Poles treated with ethanol (flint-koted barked  and unbarked) were  not  attacked until  day  9. The  most  severe attack  occurs on  the  barked  poles  (with  or  without   flint kote) Although the  attack  practically  does not  seem to occur  until day 21. Regression equation Y =27,65 + 6,93X - 5,51X , where Y =number of tunnels found on each peeling  area and  X  = depth  of peeling  (cm), represents  the development   pattern  of  the beetle galleries within  the log.